Doppelsysteme von Differenzengleichungen mit asymptotisch konstanten Koeffizienten - Naftalewitsch, A. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Г. Нафталевич. Двойные системы разностных уравнений с асимптотически постоянными коэффициентамиA. Naftalevičius. Dvilypės skirtuminių lygčių sistemos su asimptotiškai pastoviais koeficientais